Efficacy of solution-focused brief therapy versus case management for psychological distress in adolescents and young adults in a community-based youth mental health service in Singapore: protocol for a randomised controlled trial - Janhavi Ajit Vaingankar; Edimansyah Abdin; Charmaine Tang; Cheryl Yunn Shee Foo; Tianyi Hui; Nur Khairunisa Binte Ngaiman; Darshan s/o Dahjalarrajah; Yi Chian Chua; Yi Ping Lee (BMJ Open)
Introduction There are insufficient scalable, evidence-based treatments to meet increasing mental health needs of young people. Offering interim, brief interventions for young persons with psychological distress can improve access to care and mitigate adverse effects of long waiting times. This study tests the efficacy of solution-focused brief therapy (SFBT), a strength-based, goal-directed intervention, in adolescents and young adults at a community-based youth mental health service in Singapore.Methods and analysis This is a fully powered, randomised, single-centre, two-arm, parallel, superiority, controlled trial. From September 2023 to March 2025, the study will recruit 124 participants (aged 16–30) presenting at a national youth mental health service in Singapore (CHAT, Centre of Excellence for Youth Mental Health) with clinically assessed general psychological distress, subthreshold or prodromal symptoms, or a first episode of a mood disorder. Participants will be excluded if they have high risk of suicide, psychosis, cognitive impairments, or current psychological treatments. Participants will be randomised in a 1:1 ratio to receive six-session, case manager delivered SFBT or treatment as usual (TAU) case management, and be followed up for 3 months post-intervention. Participants receiving SFBT are hypothesised to have greater improvements in self-reported psychological distress, from baseline to 8 weeks, compared with the control group. Secondary outcomes are self-reported depression and anxiety symptoms, and functional impairment. The study will also explore whether SFBT is associated with increased self-efficacy and decreased hopelessness, decreased downstream referrals post-intervention, and sustained clinical gains 3 months post-intervention compared with TAU. Adverse events and clinical deterioration will be recorded and reported.Ethics and dissemination The Institute of Mental Health (IMH) Institutional Research Review Committee (reference 822–2022) and the Singapore National Health Group Domain Specific Review Board (DSRB) (reference 2023/00052) have approved the study protocol. Findings will be published in international, peer-reviewed scientific journals. Summaries will be disseminated to study funders, mental healthcare systems administrators, and clinicians.Trial registration number ISRCTN13671612 https://doi.org/10.1186/ISRCTN13671612